Teks Ucapan Yang Hormat Profesor Dato’ Dr. Daing Nasir Ibrahim Naib Canselor Universiti Malaysia Pahang Sempena Master of Business Administration Graduation Dinner 2016 - Pejabat, Naib Canselor UMP (Universiti Malaysia Pahang, 2016)
Expoconvo 2016 is to be officially launched tomorrow evening, and on convocation eve this Friday, another dinner will be held, this time with our special guests, strategic partners, award recipients and senior UMP officials, as the final prelude for the great event on the following morning.